The Logos of the Communicating Silence - Brejdak, Jaromir (Ruch Filozoficzny, 2024)
The following thesis is an attempt to establish the communicative dimensions of silence. In it I put forward a thesis in the spirit of Martin Buber's philosophy of dialogue and Max Scheler's phenomenology of emotion , according to which true dialogue does not convey specific content, but modes of existence born of the experience of presence. This kind of normative transmission of existence makes communication a communion. Underlying tacit communication are various forms of affection , through which emotionality becomes one of the main dimensions of communicating silence.